2016
DOI: 10.1161/atvbaha.116.307373
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Attenuate NADPH Oxidase-Dependent High Mobility Group Box 1 Production and Inhibit Abdominal Aortic Aneurysms

Abstract: Objective Abdominal aortic aneurysm (AAA) formation is characterized by inflammation, smooth muscle activation and matrix degradation. This study tests the hypothesis that macrophage-produced high mobility group box1 (HMGB1) production is dependent on NADPH oxidase (Nox2) which leads to increase in IL-17 production resulting in AAA formation and that treatment with human mesenchymal stem cells (MSCs) can attenuate this process thereby inhibiting AAA formation. Approach and Results Human aortic tissue demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 38 publications
3
52
0
1
Order By: Relevance
“…In addition to shear stress, growth factors and cytokines have been shown to directly regulate SMC differentiation, and the expression levels of cytokines and growth factors are likewise altered during differentiation of mesenchymal stem cells, for example. 117 Importantly, it was found that oxidative stress is essential for stem cells to differentiate into SMCs. 118 ROS are highly reactive molecules that are generated, for example, after interaction of integrins, extracellular matrix, and cytokines.…”
Section: Stem/progenitor Cellsmentioning
confidence: 99%
“…In addition to shear stress, growth factors and cytokines have been shown to directly regulate SMC differentiation, and the expression levels of cytokines and growth factors are likewise altered during differentiation of mesenchymal stem cells, for example. 117 Importantly, it was found that oxidative stress is essential for stem cells to differentiate into SMCs. 118 ROS are highly reactive molecules that are generated, for example, after interaction of integrins, extracellular matrix, and cytokines.…”
Section: Stem/progenitor Cellsmentioning
confidence: 99%
“…55 Their recent work provided insights that mesenchymal stem cell infusion inhibited macrophage-produced high mobility group box 1 production and diminished release of proinflammatory cytokines, thereby preventing elastase-induced AAAs. 56 …”
Section: Abdominal Aortic Aneurysmsmentioning
confidence: 99%
“…Increasing evidence supports that MSCs provide the therapeutic potential to inhibit AA progression via paracrine effect. [9][10][11][12] BM-MSC-derived conditioned medium (MSCs-CM) is thought to be a potent secretory component of BM-MSCs containing specific cytokines, growth factors and small RNAs, which play an important role in MSC-mediated therapeutic effects. 13 Several recent studies have demonstrated that administration of MSCs-CM was as effective as BM-MSCs treatment itself in animal models of tissue injury and inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%